Soaking Water Of Pineapple Peel (Ananas comocus L. Merr) Solution On Reducing Formaldehyde Levels In Salted Fish - Sugiana; narwati; Marlik; Rusmiati (International Journal of Advanced Health Science and Technology, 2024)
ABSTRACT Formaldehyde in salted fish processing is used to extend the shelf life of salted fish, potentially causing harmful effects on health. Before processing, such as soaking using pineapple peels can be done to reduce formaldehyde levels so that it is not harmful to health. The purpose of the study was to determine the decrease in formaldehyde levels in salted fish before and after soaking using a pineapple peel solution. This research is a pre-experimental study with a group Pretest and Posttest Design. The object of research is salted fish soaked in pineapple peel solution concentrations of 20%, 40%, 60%, and 80% with 4 replications. Soaking time is done for 60 minutes. The method of checking formaldehyde levels using the spectrophotometer method. The data that has been obtained is then analyzed using a paired t-test. The results of the examination of formaldehyde levels of salted fish before soaking amounted to 13.30 mg/kg. In contrast, after soaking the pineapple peel solution concentration of 20%, 40%, 60%, and 80% respectively amounted to 6.58 mg/kg, 4.16 mg/kg, 0.15 mg/kg, and 0.11 mg/kg, and tap water of 8.14 mg/kg. The Paired t-test obtained the P < α (0.05), meaning there is a significant difference in decline. The highest formaldehyde content reduction of 99.14% occurred in the treatment of soaking in pineapple peel solution with a concentration of 80% with a soaking time of 60 minutes. There is a significant difference between formaldehyde levels in salted fish before and after soaking using a pineapple peel solution. The use of pineapple peel solution can be an alternative effort in reducing formaldehyde levels in salted fish before processing for consumption and using other fruit peels with different concentration variations and different soaking times in salted fish.